An Analysis and Research on the Characteristics of Chinese Jin Opera Costume Art - Li Zifei,; Aris, Asliza; Nor, Zainudin (Advances in Humanities and Contemporary Studies, 2024)
Originating from the heart of Shanxi, China, Jin opera, known as "Zhong Lu Bang Zi," manifests as a regional opera that has assimilated the melodious songs and rhythmic tunes of the Shanxi populace and the central region. Consequently, it has matured into a distinctive genre of operatic performance. Correspondingly, the traditional costumes worn by the characters in Jin opera have evolved in unison with the development of Chinese opera, ultimately giving rise to a distinguished system of attire during the illustrious Chinese Ming Dynasty the traditional costume designs within Jin opera intricately reflect a distinct structure, resplendent with a vibrant palette and ornate patterns, seamlessly carrying forth the quintessential features intrinsic to ancient Chinese opera costumes. To illuminate this subject matter, this research endeavors to adopt a qualitative research methodology, meticulously analyzing the myriad styles, colors, and fabrics employed in Jin opera costumes. Moreover, it diligently categorizes and delves into the inherent characteristics embodied by these costumes during Jin opera performances. By employing poignant examples as illustrative evidence, this study succinctly encapsulates the artistic attributes that hallmark Jin opera costumes. Furthermore, it expounds upon the present state of research pertaining to Jin opera costumes, while concurrently furnishing theoretical frameworks to guide their sustainable development.